2015
DOI: 10.1016/j.redox.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Epalrestat increases glutathione, thioredoxin, and heme oxygenase-1 by stimulating Nrf2 pathway in endothelial cells

Abstract: Epalrestat (EPS) is the only aldose reductase inhibitor that is currently available for the treatment of diabetic neuropathy. Recently, we found that EPS at near-plasma concentration increases the intracellular levels of glutathione (GSH) in rat Schwann cells. GSH plays a crucial role in protecting endothelial cells from oxidative stress, thereby preventing vascular diseases. Here we show that EPS increases GSH levels in not only Schwann cells but also endothelial cells. Treatment of bovine aortic endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
(68 reference statements)
0
24
0
1
Order By: Relevance
“…Our study of bovine aortic endothelial cells revealed that LY294002, an inhibitor of phosphatidylinositol 3-kinase, 30) abolished the EPS-stimulated GSH synthesis, suggesting that the kinase is associated with Nrf2 activation induced by EPS. 21) In contrast, in the case of Schwann cells, it was unlikely that the action of EPS was associated with the kinase because LY294002 had no influence on EPS-stimulated GSH synthesis (data not shown). On the other hand, Nrf2 was degraded by the ubiquitin-proteasome system and proteasome inhibitors enhanced HO-1 mRNA and protein accumulation.…”
Section: )mentioning
confidence: 90%
See 1 more Smart Citation
“…Our study of bovine aortic endothelial cells revealed that LY294002, an inhibitor of phosphatidylinositol 3-kinase, 30) abolished the EPS-stimulated GSH synthesis, suggesting that the kinase is associated with Nrf2 activation induced by EPS. 21) In contrast, in the case of Schwann cells, it was unlikely that the action of EPS was associated with the kinase because LY294002 had no influence on EPS-stimulated GSH synthesis (data not shown). On the other hand, Nrf2 was degraded by the ubiquitin-proteasome system and proteasome inhibitors enhanced HO-1 mRNA and protein accumulation.…”
Section: )mentioning
confidence: 90%
“…In our previous reports, we have described that EPS activates Nrf2 in rat Schwann cells and bovine aortic endothelial cells. 10,21) Schwann cells, the myelin forming cells in the peripheral nervous system, are crucial for the proper function and maintenance of peripheral nerves.…”
Section: Effect Of Eps On Ho-1 Levels and Nrf2 In Sh-sy5y Cellsmentioning
confidence: 99%
“…Rice is widely consumed around the world and rice-derived peptides are reported to have various biological effects such as anti-microbial activity, (8,9) anti-oxidative activity (10,11) and dipeptidyl peptidase-IV-inhibitory activity. (12,13) Compounds that have so far been reported to increase intracellular glutathione levels include silymarin, (14) cyanohydroxybutene, (15) α-naphthoflavone, (16) apocynin, (17) epalrestat, (18,19) ribose-cysteine, (20) β-carotene, (21) noradrenaline, (22) and lactacystin. (23) In a previous study, we demonstrated that rice-derived peptides (RP), obtained from commercial rice proteins using a commercial protease from Aspergillus oryzae , inhibit dipeptidyl peptidase-IV.…”
Section: Introductionmentioning
confidence: 99%
“…Four plant-based polyphenols -fisetin, rhamnetin, pyrogallin and purpurogallin-4-carboxylic acid -are active in the Keap1-Nrf2 cellular reporter assay, but only two of them -fisetin and pyrogallin -boost PMM2 enzymatic activity. Several reports indicate that epalrestat activates NRF2 in cultured cells (Yama et al, 2016;Yama et al, 2015). Using quantitative RT-PCR, we showed that epalrestat treatment of pmm-2 F125L/F125L homozygote worms modestly upregulates SKN-1 transcripts.…”
Section: Discussionmentioning
confidence: 63%